2013
DOI: 10.1007/s00396-013-3036-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-stimulus-responsive hydrogels of cationic surfactants and azoic salt mixtures

Abstract: New hydrogels having high water content, ∼96 wt%, composed of cationic surfactants, alkyltrimethylammonium bromides (C n TAB, n=12,14,16,and 18), and a small dye molecule, sodium azobzenzene 4,4′-dicarboxylic acid (AzoNa 2 ), was firstly obtained. The three-dimensional network structures of hydrogels were determined by transmission electron microscopy images, scanning electron microscopy images, 1 H nuclear magnetic resonance, and small-angle X-ray scattering measurements. The mechanism of hydrogel formation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…The authors found that UV irradiation or the addition of a salt and an acid results in a gel–sol transition, while the addition of a base hardly changes the hydrogel, suggesting that it is important to maintain the ionic state of 50 for the hydrogelation. 296 Ward et al reported that amphiphilic guanidinium alkylbenzenesulfonates 51 exhibit lyotropic behavior in aqueous solvents. At a relatively high concentration, 10 wt %, 51 self-assembles to form a lamellar structure and results in hydrogels.…”
Section: Molecular Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that UV irradiation or the addition of a salt and an acid results in a gel–sol transition, while the addition of a base hardly changes the hydrogel, suggesting that it is important to maintain the ionic state of 50 for the hydrogelation. 296 Ward et al reported that amphiphilic guanidinium alkylbenzenesulfonates 51 exhibit lyotropic behavior in aqueous solvents. At a relatively high concentration, 10 wt %, 51 self-assembles to form a lamellar structure and results in hydrogels.…”
Section: Molecular Designmentioning
confidence: 99%
“…In a typical example, 49 and 50 in a 2:1 ratio form a hydrogel at a concentration of about 4.0 wt %. The authors found that UV irradiation or the addition of a salt and an acid results in a gel–sol transition, while the addition of a base hardly changes the hydrogel, suggesting that it is important to maintain the ionic state of 50 for the hydrogelation . Ward et al reported that amphiphilic guanidinium alkylbenzenesulfonates 51 exhibit lyotropic behavior in aqueous solvents.…”
Section: Molecular Designmentioning
confidence: 99%
“…The LMWGs can form random three-dimensional networks and cavities in which liquids (lubricant oils) are trapped through H-bonding, π–π stacking, hydrophobic interaction, van der Waals force, London dispersion forces, and electrostatic interaction. , A variety type of molecules have been used as the LMWGs, for example amino acid, , fatty acid derivatives, quterary ammonium salts, , urea, , anthracene derivatives, organometallic compounds, steroid derivatives, and so on. They can either gelate water or organic solvents and ILs, forming hydrogels, organogels, ionogel, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The rheological property can be evaluated by measuring the viscoelasticity and the mechanical strength of the gels, and which can provide guidelines for gel applications . The solid‐like network structure of gels, when implanted to be sheared under an increasing stress, will break suddenly at a critical shear stress, τ*, beyond which a Newtonian‐like flow occurs .…”
Section: Resultsmentioning
confidence: 99%